Using auto-ethnography to bring visibility to coloniality. (November 2021) - Hernandez-Carranza, Giovanni; Carranza, Mirna; Grigg, Elizabeth
This article traces how coloniality traps research and researchers in the Global North into maintaining the rigidity of its politics and logics through the meaning process. As International Social Work continues to gain popularity, supporting the proliferation of research across borders, the theoretical underpinnings must be unpacked with the context of the collaboration and the cultures involved that give meaning to both. The crux of the article rests within the implications for qualitative research in social work—both within, and across borders as a way of promoting social justice with marginalized communities. It also provides new possibilities for transcending and translating methodologies across the fields of social work and anthropology. To illustrate how research operates under the rubric of coloniality, this article uses autoethnography to uncover the on-the-ground realities of working across localities. The auto-ethnography revealed that despite the goal of sharing control of the research process, tensions related to coloniality emerged. As a result of working in different localities, each team's processes became distinct—as it was informed by different historical, economic and geopolitical processes.